Workflow automation with Microsoft Power Automate : use business process automation to achieve digital transformation with minimal code - Guilmette, Aaron (Expert insight., 2022)
Make your organization more productive and simplify your workflow by using Microsoft Power Automate for business process automation Key Features Learn the latest in Power Automate with updated user interface visuals and new technology included Apply practical knowledge like managing user inputs, documents, approvals, and database storage Create flows that integrate with services both inside and outside the Microsoft 365 ecosystem Book Description MS Power Automate is a workflow automation tool built into MS 365 to help businesses automate repetitive tasks or trigger business processes without user intervention. It is a low-code tool that is part of the Microsoft applications framework, the Power Platform. If you are new to Power Automate, this book will give you a comprehensive introduction and a smooth transition from beginner to advanced topics to help you get up to speed with business process automation. Complete with hands-on tutorials and projects, this easy-to-follow guide will show you how to configure automation workflows for business processes between hundreds of applications, using examples within Microsoft and including third-party apps like Dropbox and Twitter. Once you understand how to use connectors, triggers, and actions to automate business processes, you'll learn how to manage user input, documents, and approvals, as well as interact with databases. This edition also introduces new Power Automate features such as using robotic process automation (RPA) to automate legacy applications, interacting with the Microsoft Graph API, and working with artificial intelligence models to do sentiment analysis. By the end of this digital transformation book, you'll have mastered the basics of using Power Automate to replace repetitive tasks with automation technology. What you will learn Learn the basic building blocks of Power Automate capabilities Explore connectors in Power Automate to automate email workflows Discover how to make a flow for copying files between cloud services Configure Power Automate Desktop flows for your business needs Build on examples to create complex database and approval flows Connect common business applications like Outlook, Forms, and Teams Learn the introductory concepts for robotic process automation Discover how to use AI sentiment analysis Who this book is for This book is excellent for information workers and Power users who are looking to automate repetitive tasks for their organizations or for projects they are undertaking. To make the most of this book you should have some basic exposure to the MS 365 platform.